2022
DOI: 10.1097/cce.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Integrity, Burnout, and Intent to Leave the Job in Critical Care Nurses and Physicians

Abstract: OBJECTIVES: To describe relationships between compromised integrity (CI), burnout, and intent-to-leave (ITL) practice in critical care (CC) and noncritical care (non-CC) nurses and physicians. DESIGN: CC nurses (RNs) and physicians (MDs) from the American Medical Association Coping with COVID survey were matched by gender, race, years in practice, and role with non-CC clinicians to determine likelihood of ITL in relation to burnout and CI. SETTING: U.S. Healthcare organizations; July—December 2020. SUBJE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 34 publications
(48 reference statements)
2
40
0
Order By: Relevance
“…A perception that patients are not being cared for humanely or that care given is inappropriate [5,23] can promote disillusion and frustration. End-of-life care, in particular, is not always as good as it could or should be for ICU patients.…”
Section: • Intellectual Stimulation and Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A perception that patients are not being cared for humanely or that care given is inappropriate [5,23] can promote disillusion and frustration. End-of-life care, in particular, is not always as good as it could or should be for ICU patients.…”
Section: • Intellectual Stimulation and Professional Developmentmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) crisis has been followed by a serious increase in the shortage of intensive care unit (ICU) personnel, especially nurses, exacerbating a problem that pre-dated the pandemic… and this on a global scale. The reasons are not difficult to elucidate and primarily relate to the prolonged, excessive workload during the pandemic period, often with denial of vacation time; the significant emotional burden associated with the high patient death rate; and the moral distress associated with being unable to provide the usual high quality standard of care, because of the sheer numbers of patients being admitted [1][2][3][4][5]. Personal anxieties around catching the virus and/or passing it on to one's family, and restrictions and limitations associated with the strict safety measures, including reduced communication and contact with patients and their relatives that resulted in a de-humanizing of care, added to the physical and mental exhaustion felt by healthcare staff [1-4, 6, 7].…”
mentioning
confidence: 99%
“…The hierarchical regression analysis has confirmed that higher morally distressing experiences led to severe symptoms of moral injury among our respondents. This sheds new insight and can be worthy of consideration for the nursing field in general as a moral injury might be misunderstood under moral distress or when related to the consideration or decision to leave a profession and position cofounded with burnout (Hancock et al, 2020; Karakachian & Colbert, 2019; Laurs et al, 2019; LeClaire et al, 2022; Linzer & Poplau, 2021; Naboureh et al, 2021) failing to treat it timely and adequately. If left unaddressed, such an issue will affect the mental health of health care workers and, subsequently their tendency to resign from their employment or occupation.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of COVID-19 on the risk of burnout and intention-to-leave the job and the profession seems to be increased among ICU nurses compared to before the pandemic and after the first wave (Bruyneel et al, 2021b;Butera et al, 2021;Vermeir et al, 2018). This can be explained by several elements including the lack of personal protective equipment, fear of being contaminated, increased mortality rates compared to normal, successive waves, societal expectations, and accumulation over time (Bruyneel et al, 2021b;Khan et al, 2022;LeClaire et al, 2022;Moradi et al, 2021). Hospitals have implemented, in a variable and heterogeneous way, several internal measures (e.g., psychologists, debriefing, meditation) which may have influenced the results with ICU nurses in Belgium (Paquay et al, 2022;Servotte et al, 2020;Van Den Heede et al, 2022).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…As of this time, the country has experienced seven waves, mainly in the autumn and winter of December 2021 (Dellicour et al, 2021;Molenberghs et al, 2020;Natalia et al, 2022). During the COVID-19 pandemic, frontline nurses were exposed to higher levels of stress and traumatic events that could increase the risk of burnout (Guixia and Hui, 2020;Hu et al, 2020;LeClaire et al, 2022;Moradi et al, 2021). A study conducted after the first wave of COVID-19 showed a high risk of emotional exhaustion (38%) among French-speaking ICU nurses in Belgium (Bruyneel et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%